Tennis Play and Stay – Case studies from South America and West, Central and North Africa - Kist, Cesar; Makhlouf, Amine Ben (ITF Coaching & Sport Science Review, 2017)
Tennis is a game; therefore, it’s obvious that we need to, as coaches, develop a tactical and playful learning process if we want to retain players in the sport for many years. It´s fundamental to have more players in the game, to build better players, to produce top players, to keep the beginners in the game (kids, teens and adults). Tennis Play and Stay is a reality.